Relation of Epstein Barr virus with interleukin-10 Levelamongmen with Prostate Cancer in Ramadi City (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study aimed at evaluating the relation of Epstein Barr virus (EBV)with level of interlukin-10 (IL-10) in men withprostatecancer(PC). The study was carried out in Ramadi city from 12th of January to 12th of September 2018, and included a total of 95 women withbreast cancerwho admitted to oncology clinic ofRamadi Teaching Hospital whose ages were between 40-80 years. Patients were investigated for detection of EBV by using Real Time PCR and interleukin-10 (IL-10) by ELISA technique.The rate of prostate cancer men with EBV was (16.84%). The highest rate of prostate cancer menwas within the age group 50-59 years with no significant relation between prostate cancer and age. The study showed that the highest means of IL10 level (19.43 pg/ml) were found in prostate cancer men without EBV.There was significant difference (P value
Keywords: Prostate cancer, EBV, IL-10, Ramadi.